Pengembangan Komik Fisika Materi Kemagnetan Sebagai Media Pembelajaran Siswa SMPN 1 Maumere - Feka, Maria Goroliva; Donuata, Pujianti Bejahida; Koten, Florentinus P. N. (Kappa Journal, 2023)
Comics are light reading and are preferred by teenagers and children, because comics are full of imagination and pictures. This research tries to inform theories in the form of writing and developed in a comic media. The purpose of this research is to make physics comics of magnetic material using comic media, and make students understand about magnetic materials. The research method carried out is R&D, the teacher as a researcher who refers to the model with the 4-D definition, Stages, design, development, dissemination. The sample was ninth grade junior high school students, while the research instruments were physics comics and questionnaire distribution. The success of this physics comic is seen from the answers of students filling out a questionnaire of student interest in learning with a success indicator of 80.3% which is included in the very good category. After conducting this comic trial, it succeeded in making students understand about magnetic material and students were interested in learning by using comic media.